Synthesis and Magnetic Property of a Nickel(II) Complex: [Ni(C14H14N8O2)]4(ClO4)8(H2O)8(CH3OH)0.5 - Bi, Jian-Hong; Bi, Wen-Tao; Wang, Hong-Liang; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A new self-assembled Schiff base of nickel(II) complex with the molecular formula [NiL]4(ClO4)8(H2O)8(CH3OH)0.5 {L = (6Z,15Z)-N1',N2'-bis(amino(pyridin-2-yl)methylene)- oxalohydrazide} has been synthesized and characterized by IR spectra, elemental analysis and TG measurement. The magnetic properties investigation shows that there is weak antiferromagnetic interactions between the Ni(II) ions of the complex.